Reading Disabilities in children with Specific Language Impairment - Soriano-Ferrer, Manuel; Contreras-González, Mª Carmen; Corrales-Quispiricra, Carmen (Revista de Investigación en Logopedia, 2019)
The present study examined the reading performance of children with specific language impairment (SLI). Thirty children with SLI and 32 children with normal language development, matched in gender, chronological age and intelligence, were evaluated through PROLEC-R. The results of the ANOVAs indicated that both groups differ in reading performance. As a group, children with SLI had significantly lower performance, both in the accuracy and speed of words and pseudowords reading and, so they had less reading efficiency. Along the same lines, the performance of children with SLI in literal and inferential comprehension was also lower than that of children with typical development. However, an individualized analysis indicated that some children with SLI have a normal performance in the accuracy and speed of reading words and pseudowords (between 50% and 70%). However, in the case of reading comprehension, the majority of children with SLI had a significantly lower performance (87%), although about 13% had a performance within the range of normality. Hierarchical regression analysis showed that different linguistic measures -auditory comprehension, sequential auditory memory and word reading efficacy- played a predictive role in reading comprehension.
Keywords: reading; difficulties; specific language impairment